For the record: The Canton exile of the missionaries (1666-1671) by the Polish Jesuit Szpot Dunin - Meynard, Thierry (Annales Missiologici Posnanienses, 2020)
The Chinese Rites Controversy definitively shaped the history of Christianity in China. When some missionaries were exiled in Canton from 1666 to 1671, they sought to resolve their disagreement on whether certain Confucian rituals could be practiced by Chinese Christian converts but their differences ended up even more entrenched. In his unpublished history of the China mission covering the period from 1640 to 1700, the Polish Jesuit Tomasz Ignacy Szpot Dunin (1644-1713) gives an account of the discussions held in Canton. His account not only reveals previously known materials but also offers new insights on the Controversy.